Epidemiological, Clinical and Entomological Characteristics of Yellow Fever Outbreak in Darfur 2012 - Hamdi Abdulwahab Alhakimi; Omima Gadalla Mohamed; Hayat Salah Eldin Khogaly; Khalid Ahmad Omar Arafa; Waled Amen Ahmed (AIMS Press, 2015)
The study aims at analyzing the epidemiological, clinical and entomological characteristics of Darfur yellow fever epidemic. It is a descriptive, cross-sectional study. According to operational case definition, suspected yellow fever cases are included in case spread sheet with variables like age, sex, locality, occupation, status of vaccination, onset of symptoms, presenting symptoms, date of blood sampling and confirmation of diagnosis either by laboratory results or epidemiological link. Data about important entomological indices were collected by surveys conducted in 17 localities of 3 Darfur states (Central, West and south Darfur). All Darfur states (especially Central Darfur) have been affected by Yellow Fever outbreak. There is a need to review the non-specific case definition of Yellow Fever which seems to overwhelm the system during outbreaks with cases of other endemic diseases. The significant risk factors of this outbreak included male sex, adult age, outdoor occupation and traditional mining. The fatality rate was significantly associated with vaccination status. The highest fatality rate was recorded by children less than 2 years old (42.9%). Generally, increase in certain entomological indices was followed by increase in number of reported cases 7 days later. Central Darfur state was significantly higher in most studied entomological indices.